Rethinking American Music - Riis, Thomas Laurence; Browner, Tara, 1960- (Book collections on Project MUSE., 2019)
Only since the 1970s have the variety of American musical styles and sounds have been allowed to stand on their own two feet in the academic world. Recent efforts to place American music-making within new or heretofore neglected contexts are diverse and inevitably shift our consciousness about music's meaning and impact in culture. This volume contains a series of commentaries or glosses, chapters about American music broadly understood that seek especially to explore four critical factors beyond the the familiar categories defined by repertory or biography alone: the impact of performance; the role of patronage in the creation of musical objects and events; personal identity; and how larger cultural/ethnographic contexts (community values, ethnic markers, and social relations) determine certain musical results.